C. ESPEGEL - Women Architects in the Modern Movement - Muxí, Zaida (ZARCH. Journal of interdisciplinary studies in Architecture and Urbanism, 2019)
Carmen Espegel Women Architects in the Modern Movement New York: Routledge, 2018 Translation: Angela Giral